INVESTIGATION OF CONTINGENCY PATTERNS OF TEACHERS' SCAFFOLDING IN TEACHING AND LEARNING MATHEMATICS - Anwar Anwar; Ipung Yuwono; Edy Bambang Irawan; Abdur Rahman As'ari (Journal on Mathematics Education, 2017)
The purpose of this study is to investigate the patterns of scaffolding contingency in teaching and learning mathematics carried out by three teachers. Contingency patterns are obtained by examining the transcription from video recording of conversation fragments between teachers and students during the provision of scaffolding. The contingency patterns are drawn in three strategies: diagnostic strategy, intervention strategy, and checking diagnosis. The result shows that the three teachers expressed different interaction contingencies in their scaffolding activities: contingent dominant, non-contingent dominant, and pseudo-contingent. It is also found that the learning interaction performed by experienced teachers tends to be contingent dominant compared to novice teachers.Keywords:Â Contingency, Contingent Dominant, Non-Contingent Dominant, Pseudo Contingent, ScaffoldingÂ DOI: http://dx.doi.org/10.22342/jme.8.1.3410.65-76